Examining the sports participation motivation levels of physically disabled and hearing impaired athletes - Yilmaz, A.; Kirimoglu, H.; Mirze, F. (International Journal of Applied Exercise Physiology, 2020)
This study was conducted to examine the factors affecting the sports participation motivation levels of physically disabled and hearing impaired athletes concerning certain variables. The "Personal Information Form" that was developed by the researchers and the "Sports Participation Motivation Scale for Disabled Individuals (SPMSDI)", which was developed by Tekkursun et al., (2018), were used as the data collection tools. The survey forms were filled by the help of a sign language expert for the hearing impaired athletes and through one-on-one interviews with the physically disabled individuals. The sample group was comprised of 41 volunteer participants, 24 of whom were physically disabled and 17 of whom were hearing impaired individuals. The data obtained from the research were analyzed through the SPSS 20.0 package program. Mann-Whitney U test and Kruskall Wallis tests were used. Based on the findings of the study, comparing the sports participation motivation levels of the hearing impaired and physically disabled athletes with age and educational status variables, it was determined that there was statistically no significant difference in all sub-dimensions of motivation. However, it was determined that there was a statistically significant difference in favor of the physically disabled individuals in the internal and external motivation dimensions. It was determined that there was statistically no significant difference in the amotivation sub-dimension. As the conclusion, it was determined that age and educational status had no effect on the sports participation motivation level; however, it was detected that physically disabled athletes had a higher motivation level compared to the hearing impaired athletes concerning the disability type and sports branch variables. In this regard, in order to increase both the sports participation of the physically disabled and hearing impaired individuals and their persistence in sports, it can be suggested to develop policies considering the motivational factors concerning their disability types and sports branches.